Projection of older population in Malaysia by physical disability status - Muhammad Aziz; Mohd Azmi Haron; Zailan Siri; Noriszura Ismail (Universiti Kebangsaan Malaysia, 2024)
In Malaysia, the well-being of individuals with disabilities remains a concern. Addressing the situation of individuals with disabilities and the aging population is critical for the future of Malaysia. This study utilizes a multistate approach to assess the transition probability of disability among older adults in Malaysia. We utilize information from the National Health Morbidity Survey (NHMS) 2019 to parameterize a functional Markov Model and employ a cohort-component projection method for projecting the Malaysian population for 2020-2040 by disability status. The probability of becoming disabled increases with age and is higher for females than males. By 2040, it is anticipated that Malaysia will have nearly 1.7 million disabled older persons experiencing at least two of the six physical limitations delineated in the National Health Morbidity Survey 2019. With advancing age, there is a progressive increase in the likelihood of experiencing disability. The projected 13% of Malaysians aged 65 and above by 2040 emphasizes the necessity for enhanced eldercare social security.